Degradation of Hyaluronic Acid by Multiple Ultrasonic - Teng-Fei, Li; Bo-Chu, Wang; Bing, Wang (Asian Journal of Chemistry, 2011)
Ultrasonic degradation of hyaluronic acid salt solutions was investigated by a ultrasonic instrument, which is designed to make use of multiple ultrasonic oscillator simultaneously. Single source, two sources and three sources were irradiated at high frequency (1.7 MHz) and low frequency (800 kHz). The degraded samples were analyzed by gel permeation chromatography for the time evolution of the molecular weight distributions and the contents of OH• radicals were obtained as functions of sonication time. A continuous distribution kinetics model based on midpoint chain scission was developed and the limiting molecular weight and degradation rate were determined. The experimental data showed that more OH• radicals were produced in the unit time when it was irradiated with two or three sources compared with the single source, which means the degradation rate of the hyaluronic acid increased. The limiting molecular weight was decreased by multiple ultrasonic treatment. This implies that the ultrasonic degradation of hyaluronic acid is faster and more effective.